The role of Sarcocornia perennis and tidal flooding on sediment biogeochemistry in a South American wetland - Negrin, Vanesa Lorena (2013)
The roles of Sarcocornia perennis and tidal flooding on sediment biogeochemistry were evaluated within a wetland in the Bahı´a Blanca estuary. pH and Eh were measured in sediments while particulate organic carbon (POC) and dissolved inorganic nutrient concentrations were determined in porewater, at three sites with different conditions according to vegetation and flooding. Grain size was also analysed. pH varied in a narrow range (7 8.2) and was lower in the vegetated site. Eh values (50 250 mV) imply that sediment conditions were moderately reduced, in agreement with the relatively high percentage of sand; it was influenced by both factors. POC concentration was high (26.2491.62 mg/l), especially at the vegetated site. The concentrations of ammonium and nitrate were similar (21.3091.83 and 18.7793.06 mmol/l, respectively) and not affected by flooding; only nitrate was affected by vegetation. Phosphate was rather constant (13.4391.19 mmol/l) and affected mainly by flooding. Silicate was high (566.45976.06 mmol/l) and not affected by either factor. These results suggest that the sediment biogeochemistry of this environment is significantly influenced by flooding and, especially, by S. perennis, as vegetation affected a higher number of parameters.